Association Between Profile Characteristics and the Level of Aspiration of Women Dry Fish Wholesalers (Indian Journal of Extension Education, 2011)
Over the last two centuries, women’s role in Karnataka, Andhra Pradesh, Tamilnadu and Kerala reveal fisheries has been predominantly in the fish processing and that in Kerala, women workforce (45%) are dominating marketing sectors. Processing is clearly the sub sector the peeling work in prawn peeling sheds, in Tamilnadu where women are most involved in fisheries, 51 per cent of the workforce engage in fish trading and demonstrating a small majority of the workforce at 53 per 32 per cent in fish curing/drying/net making. In Karnataka cent but within an average of 11 to 75 per cent. However 44 per cent and 34 per cent of its fisherwomen are women are mostly 40 to 60 per cent of the workforce, engaged in beach work and small scale fish trading with only Greece (11%) having markedly less than 40 per respectively. Andhra Pradesh employs 32 per cent in fish cent female involvement. (Elliot, 2002). Women’s curing /drying/net making and 27 per cent in processing involvement in the management and administration element plant works.